Axial load-bearing capacities of pre-cast self-insulation walls made by foam concrete. (October 2020) - Li, Jie; Chen, Zhongfan; Chen, Wenwen
Abstract: Foam concrete with high strength and low thermal conductivity (HLFC) was developed by using a certain mix ratio, which could be used as a load-bearing structural material. The mechanical properties, thermal conductivity, impermeability, shrinkage rate as well as frost resistance properties of HLFC were tested, results showed that it could be used in hot-summer and warm-winter zone or hot-summer and cold-winter zone as wall materials. Combining the concept of energy-saving and industrialization of building, a new type of assembled self-insulation wall prefabricated by HLFC and suitable for low-rise residential buildings was proposed. In order to study the axial load-bearing capacities of the wall, two pre-cast wall specimens considering different reinforcement ratio and one cast-in-place wall as counterpart were designed. The failure mode, axial load–displacement relationship, deflections as well as the steel strains were analyzed under vertical load. Test results showed that both vertical cracks and horizontal wrinkles occurred along the height range of the HLFC self-insulation wall under axial load, and the final failure mode of every specimen was the foam concrete at the top end of the wall crushed, while all the pre-cast specimens maintained good structural integrity throughout the whole loading process. Increasing the reinforcement ratio could obviously improve the initial compressive stiffness and reduce the number of wrinkles of the specimen, and the performance gap of the fabricated HLFC wall was not obvious with post-cast ones except in the cracking load and the degradation compressive stiffness. At last, test results were compared to the calculated values according to standards as GB50010-2010, GB50003-2011 and ACI318-14. Comprehensively considering the test phenomena and mechanical mechanism of the specimens, a modified calculation formula was proposed to make an accurate prediction of the axial load-bearing capacities of the HLFC insulation wall, and the differences between the calculated values and the test results were with 3%.